Nationwide Procedural Trends for Renal Trauma Management. Issue 2 (February 2019) - Colaco, Marc; Navarrete, Roberto A.; MacDonald, Susan M.; Stitzel, Joel D.; Terlecki, Ryan P.
Abstract : Objective: To characterize national trends in procedural management of renal trauma. Background: Management of renal trauma has evolved to favor a more conservative approach. For patients requiring intervention, there is a paucity of information to characterize the nature of procedural therapy administered. Methods: A retrospective cross-sectional analysis was performed using data contained within the National Trauma Data Bank. The National Trauma Data Bank is a voluntary data repository managed by the American College of Surgeons, containing data regarding trauma admissions at 747 level I to V trauma centers throughout the United States and Canada. Participants included any patient with renal trauma requiring intervention from 2002 to 2012. They were identified according to International Classification of Diseases, Ninth Revision (ICD-9) diagnosis codes, with codes 866.00 through 866.03 for blunt renal trauma, and codes 866.10 through 866.13 for penetrating trauma. Cases were separated into those requiring nephrectomy, renorrhaphy, or endovascular repair based on ICD-9 procedure code. The number of cases performed each year and yearly trends as measured by linear regression. Results: A total of 4296 cases were reported during the study period. Of these cases, 2635 involved blunt trauma and 1661 involved penetrating injury. There was a significant increase in the percentage of cases managed by endovascular means for both blunt and penetrating trauma ( R 2 = 0.92, P < 0.01; and R 2 = 0.86, P < 0.01, respectively). This was primarily at the expense of nephrectomy, with cases showing significant decline in both groups. Conclusions: National trends for procedural management of renal trauma are toward less invasive interventions. These trends suggest favorable change towards renal preservation and decreased morbidity, potentially facilitated, in part, by improved radiographic staging and endovascular techniques, and also increased provider awareness of the safety and value of conservative management.